"It is quite conceivable that judgment is a very complicated phenomenon": Dorothy Wrinch, nonsense and the multiple relation theory of judgement. Issue 2 (4th March 2022) - Felappi, Giulia
ABSTRACT: In her paper "On the Nature of Judgment", published in 1919 in Mind, Dorothy Wrinch aimed at understanding how Russell's multiple relation theory of judgement might be made to work. In this paper we will focus on Wrinch's claim that on the theory it is impossible, as it should be, to judge nonsense. After having presented the prima facie objection to the theory created by nonsense and what we can take her solution to such a problem to imply (§1), we will show how Wrinch can resist the two main objections that have been moved to such a solution, whether as explicitly attributed to Wrinch or discussed without mentioning her. The conclusion will be, contrary to what one might be tempted to think, that even if there might be reasons to take the multiple relation theory as doomed, Wrinch was the first to show us that nonsense is not one of those reasons.